Advertisement Remove all ads

Y3 − 7y + 6 - Mathematics

Answer in Brief

y3 − 7y + 6

Advertisement Remove all ads

Solution

Let f(y) =y3 − 7y + 6 be the given polynomial.

Now, putting  y= 1,we get

`f(y) = (1)^3 -7(1) + 6 = 1-7 +6`

        ` = 7-7 = 0`

Therefore, (y-1)is a factor of polynomial f(y).

Now,

`f(y) = y^2 (y-1) + y(y-1) -6(y-1)`

        ` = (y-1){y^2 + y y-6}`

        ` = y-1{y^2 + 3y - 2y - 6}`

        `= (y -1)(y+2)(y+3)`

Hence (y-1),(y-2) and (y+3)are the factors of polynomial f (y).

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 6 Factorisation of Polynomials
Exercise 6.5 | Q 7 | Page 33
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×